2016
DOI: 10.1097/ajp.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Hurt

Abstract: The current study results indicate that participants' pre-Cyberball unpleasantness threshold is related to their responsiveness to social distress and that physical pain may be modulated by social events. Further studies are needed to clarify the clinical relevance of these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
2
2
1
Order By: Relevance
“…This finding contrasts with a recent study by Canaipa et al62 who reported lower pain intensity ratings for socially included participants. Unlike us, however, they applied noxious electrical stimuli instead of thermal stimuli which might account for the different results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding contrasts with a recent study by Canaipa et al62 who reported lower pain intensity ratings for socially included participants. Unlike us, however, they applied noxious electrical stimuli instead of thermal stimuli which might account for the different results.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is consistent with a study reporting increased psychological and physiological reactivity for individuals with chronic life stress after being challenged with an acute psychological stressor 61. It is also in line with previous research demonstrating that chronic life stress and other social stressors (eg, social exclusion) may cause hyperalgesia and increase physical pain distress 21,22,6266. The underlying mechanisms of this finding are not clear.…”
Section: Discussionsupporting
confidence: 90%
“…The finding that patients reporting clinically significant chronic pain also had 26% higher odds of perceived rejection supports literature elucidating the link between social rejection and physical pain (23). Human laboratory experiments have suggested a direct relationship between social rejection and reports of pain unpleasantness (24) and that physical pain is reduced by social experiences, such as inclusion (25).…”
Section: Discussionsupporting
confidence: 67%
“…Cyberball exclusion results in decreased cold pain threshold and tolerance compared to inclusion in HC, supporting the notion that the positive emotions associated with inclusion reduce pain perception, while correspondingly the negative emotions linked with exclusion induce pain hypersensitivity. 37 39 This result provides us with new behavioral evidence that improves our understanding of the relationships between social pain and a specific type of physical pain.…”
Section: Discussionmentioning
confidence: 83%